The anti-intellectual presidency the decline of presidential rhetoric from George Washington to George W. Bush - Lim, Elvin T. 1976- (New York Oxford University Press, 2008)
Elvin Lim draws on interviews with more than 40 presidential speechwriters to investigate this relentless qualitative decline, over the course of 200 years, in our presidents' ability to communicate with the public.
Keywords: Presidents -- United States -- History; Presidents -- United States -- Language -- History; Presidents -- United States -- Intellectual life -- History; Rhetoric -- Political aspects -- United States -- History; Communication in politics -- United States -- History; Political oratory -- United States -- History; United States -- Politics and government; United States -- Intellectual life